Coronary angiographic profile of Nepalese people A study of 450 cases in SGNHC - Regmi, S; Malla, R; Rajbhandari, S; KC, MB; Sharma, D; Bhatt, Y; Rajbhandari, R; Limbu, YR; Koirala, B; Kansakar, S (Nepalese Heart Journal, 2004)
Coronary Artery disease (CAD) remains a major health problem. Stable angina, unstable angina and myocardial infarction are the major manifestations of CAD. This study is aimed to assess the coronary artery profile in these groups and its relation to the major conventional risk factors and the distribution of the disease in differant ethnic group of Napalase population.